ANALISIS YURIDIS PENANGANAN TINDAK PIDANA PEMILU DI INDONESIA - Azhar, Yulham; Junita Melo, Isye; Leonardo Lombok, Lesza (At-Tanwir Law Review, 2025)
An election with integrity is the foundation of democracy, as stipulated in Article 22E paragraph (1) of the 1945 Constitution, which mandates that elections must be direct, general, free, confidential, honest, and fair (LUBER-JURDIL principles). However, the implementation of elections often faces various challenges, including election-related crimes such as vote-buying, campaigning outside the designated schedule, and administrative violations that threaten the integrity of the democratic process. Using a normative legal research method, the findings show that the Election Law contains approximately 67 articles related to election offenses. However, several of these articles include criminal elements that are difficult to prove factually, such as Articles 492, 494, 495, 513, 515, 518, and 545. The handling of election crimes is carried out through the Integrated Law Enforcement Center (Sentra Gakkumdu), which involves coordination among the Election Supervisory Board (Bawaslu), the Police, and the Public Prosecutor’s Office at both national and regional levels. Despite this institutional coordination, the effectiveness of law enforcement remains low due to differing perceptions and working patterns among the institutions involved.